Update in drug delivery system - Ensminger, William D.;Selam, Jean-Louis ([Mount Kisco, N.Y. ] : Futura Publishing Company, 1989)
This book reports and expands upon the major presentations of the '88 Drug delivery system symposium, a satellite congress of cardiostim 88.
I. Devices and biocompatibility -- II. Application in diabetes mellitus and endocrinology -- III. Application in oncology -- IV. Application in cardiology.
Includes index.
Keywords: DRUG INFUSION PUMPS